Peranan Kualitas Lingkungan Kerja Dalam Meningkatkan Kinerja Karyawan dan Kepuasan Kerja - Sahara, Laila Alvi; Kuswinarno, Mudji (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article sets out to examine the quality of the work environment as it plays a crucial role in improving employee performance and satisfaction. This research examines the various aspects that can influence the work environment, both physical and non-physical, and the impact on employee productivity. By creating an inclusive work environment that supports work-life balance, companies can not only improve employee performance, but also reputation in the eyes of customers and business partners. This article is based on a literature review study. This technique is used for the purpose of revealing various theories related to the problem under study as reference material for research results. According to Robbins, 2012 says “employees who have a high level of job satisfaction will tend to be more committed and contribute and have high dedication to the company and ultimately have the willingness to work harder and more productively. Likewise, employees with low levels of job satisfaction tend to turnover, as well as decreased discipline and work productivity”. In conclusion, it shows that investment in the quality of the work environment is an investment in human resources that will have a positive impact on the company in the long run.